Germination Enhances Phytochemical Profiles of Perilla Seeds and Promotes Hair Growth via 5α-Reductase Inhibition and Growth Factor Pathways - Anurak Muangsanguan; Warintorn Ruksiriwanich; Pichchapa Linsaenkart; Pipat Tangjaidee; Korawan Sringarm; Chaiwat Arjin; Pornchai Rachtanapun; Sarana Rose Sommano; Korawit Chaisu; Apinya Satsook; Juan Manuel Castagnini (Biology, 2025)
Seed germination is recognized for enhancing the accumulation of bioactive compounds. Perilla frutescens (L.) Britt., commonly known as perilla seed, is rich in fatty acids that may be beneficial for anti-hair loss. This study investigated the hair regeneration potential of perilla seed extracts—non-germinated (NG-PS) and germinated in distilled water (0 ppm selenium; G0-PS), and germinated with 80 ppm selenium (G80-PS)—obtained from supercritical fluid extraction (SFE) and screw compression (SC). SFE extracts exhibited significantly higher levels of polyphenols, tocopherols, and fatty acids compared to SC extracts. Among the germinated groups, G0-PS showed the highest bioactive compound content and antioxidant capacity. Remarkably, treatment with SFE-G0-PS led to a significant increase in the proliferation and migration of hair follicle cells, reaching 147.21 ± 2.11% (p < 0.05), and resulted in complete wound closure. In addition, its antioxidant and anti-inflammatory properties were reflected by a marked scavenging effect on TBARS (59.62 ± 0.66% of control) and suppressed nitrite amounts (0.44 ± 0.01 µM). Moreover, SFE-G0-PS markedly suppressed SRD5A1-3 gene expression—key regulators in androgenetic alopecia—in both DU-145 and HFDPCs, with approximately 2-fold and 1.5-fold greater inhibition compared to finasteride and minoxidil, respectively. Simultaneously, it upregulated the expression of hair growth-related genes, including CTNNB1, SHH, SMO, GLI1, and VEGF, by approximately 1.5-fold, demonstrating stronger activation than minoxidil. These findings suggest the potential of SFE-G0-PS as a natural therapeutic agent for promoting hair growth and preventing hair loss.